1999
DOI: 10.1038/sj.onc.1202383
|View full text |Cite
|
Sign up to set email alerts
|

Three distinct domains in TEL-AML1 are required for transcriptional repression of the IL-3 promoter

Abstract: A cytogenetically cryptic (12;21) translocation is the most common molecular abnormality identi®ed in childhood acute lymphoblastic leukemia (ALL), and it generates a chimeric TEL-AML1 protein. Fusion of the Helix-Loop-Helix (HLH) (also called the pointed) domain of TEL to AML1 has been suggested to convert AML1 from a transcriptional activator to a repressor. To de®ne the structural features of this chimeric protein required for repression, we analysed the transcriptional activity of a series of TEL-AML1 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…In this assay, TEL-AML1 shows only weak DNA binding, the binding being more readily visualized upon supershifting of the complex using an anti-HA monoclonal antibody (mAb) (Figure 3). In agreement with previous studies Uchida et al, 1999), full length AML1 and the D214, D289 and DHLH mutants, all showed enhanced DNA binding in comparison with TEL-AML1, Figure 1 TEL-AML1 deletion mutant constructs. Depicted are the wild-type TEL and AML1 proteins, the TEL-AML1 fusion protein and various mutant TEL-AML1 proteins that lack the HLH or CR domains of TEL, the RHD of AML1, two deletions of the transactivation domain and C-terminal amino acids of AML1, or contain an RHD point mutation.…”
Section: Expression Of Domain Deletion Mutants Of Tel-aml1 Using Retrsupporting
confidence: 92%
See 4 more Smart Citations
“…In this assay, TEL-AML1 shows only weak DNA binding, the binding being more readily visualized upon supershifting of the complex using an anti-HA monoclonal antibody (mAb) (Figure 3). In agreement with previous studies Uchida et al, 1999), full length AML1 and the D214, D289 and DHLH mutants, all showed enhanced DNA binding in comparison with TEL-AML1, Figure 1 TEL-AML1 deletion mutant constructs. Depicted are the wild-type TEL and AML1 proteins, the TEL-AML1 fusion protein and various mutant TEL-AML1 proteins that lack the HLH or CR domains of TEL, the RHD of AML1, two deletions of the transactivation domain and C-terminal amino acids of AML1, or contain an RHD point mutation.…”
Section: Expression Of Domain Deletion Mutants Of Tel-aml1 Using Retrsupporting
confidence: 92%
“…To determine which domains are required for TEL-AML1 activity in vitro and in vivo, we generated a number of deletion mutants based on previous studies (Fenrick et al, 1999;Uchida et al, 1999;Guidez et al, 2000) (Figure 1). These studies found that deletion of the runt homology domain (RHD) domain abolished TEL-AML1 binding to AML1 consensus sequences, whereas deletions of the C-terminal transactivation domain of AML1 or the HLH domain of TEL did not affect the ability of TEL-AML1 to bind to DNA (Uchida et al, 1999).…”
Section: Expression Of Domain Deletion Mutants Of Tel-aml1 Using Retrmentioning
confidence: 99%
See 3 more Smart Citations